The Effectiveness of Using Concept Mapping Strategy on Learning English Grammar Rules for English Foreign Language Learners - Shaman, Suda Nasser Hamad (Journal of Educational and Psychological Sciences, 2021)
The purpose of this quasi-experimental study is to investigate the effectiveness of applying concept mapping strategy to improve the performance skills and retention of grammar rules for English foreign language learners. The research was conducted on seventy-two undergraduate students at King Khalid University in the Aseer region in Saudi Arabia. Students were enrolled in two classes and each class was randomly assigned to either experimental or control group. Each group consisted of 36 students. The experimental group was taught with the concept mapping strategy, while the control group was taught with the traditional method. Both groups were provided with pre-test, taught with assigned treatment, and were given post-test. Then, the experimental group was provided with the retention test to examine the strategy impact on the long-term learning. The results showed that there were statistically significant differences between both groups in the post-test where the concept mapping group scored higher. Further, there were statistically significant differences between experimental group scores in the post-test and the retention test, where their scores increased in the retention test. Based on the findings of this study, teachers are encouraged to apply concept mapping strategy in their teaching and train students to create their own maps.
Keywords: Concept mapping; EFL; English grammar